Analisis Proses Morfologi pada Kolom Show dan Selebriti di Koran Harian Jawa Pos Edisi Juni 2022 - Miftakhul Jannah; Sugianti Sugianti; Ilmiyatur Rosidah (Pusat Riset dan Inovasi Nasional, 2022)
This research discusses the morphology process that aims to identify forms of affixation, reduplication, and composition in the use of vocabulary in news texts in the Show & Celebrity column of the Jawa Pos Daily Newspaper June 2022 Edition. The approach in this study is to use a descriptive qualitative approach. Data collection is done by using observation techniques or observations that are observed through news texts and note-taking techniques. The results of this study include, (1) there are 18 data on the use of affixation, namely, prefix ber-, tar, Me-, and prefix di-, clofix Me-kan, clofix Me-i; (2) there are 2 data on the use of reduplication, namely songs and albums; and (3) there is 1 data on the use of composition, namely music videos.